ANALISIS KOMUNIKASI MATEMATIS SISWA SMP PADA MATERI SEGI EMPAT - Dilla, Risa Sapta; Adriati, Nuraeni; Novtiar, Chandra (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2018)
This study has purpose to describe the achievement of students' mathematical communication with observation and interview. In this study, the method used is descriptive qualitative with the subject of 30 students SMPN 2 Ngamprah class VII. The instrument consists of 4 test questions. The result of the research is the percentage indicator of ability to connect the real object and the image into the form of mathematical idea is 41,67%, arrange conjecture, make argument, and generalize percentage of ability equal to 49,17%, explain idea, mathematical situation in writing by using picture ie reaching 57.78%, declaring everyday events in language or mathematical symbols, the percentage of ability is 24.67%